Notaris Dalam Pembuatan Akta Kontrak Yang Berlandaskan Prinsip Kehati-hatian - Khafid Setiawan; Bhim Prakoso; Moh. Ali (Faculty of Law, University of Jember, Indonesia, 2021)
The development of the business world is always increasing to support development. The position of a notary as a functionary in society is considered an official place where advice can be obtained. Everything that is written and determined is correct and official producer officials are legally binding documents, especially documents related to contracts that occur in the community. The number of transactions carried out by business actors requires legal certainty in contracts or agreements made by the parties business-related. Thus, contracts play an important role in doing business in Indonesia. This condition is the background of this research in order to determine the position of the notary in making contract deeds.